Two new species and a new genus of Calloporidae (Bryozoa: Cheilostomata) from the Southwest Atlantic - Gappa, Juan López; Liuzzi, María G. (Zootaxa, 2013)
The family Calloporidae occupies a basal position in the classification of the Cheilostomata, the relatively simple callop-orid morphology seeming to be the basic pattern for the adaptive radiation of cheilostome bryozoans. The ovicells of the Calloporidae may be formed by the maternal zooid or the distal zooid, which can be an autozooid, a vicarious avicularium or a kenozooid. Examination of new calloporid material from the southern Patagonian shelf revealed the existence of two new species and a new genus. Kenoaplousina fissurata gen. nov., sp. nov. is characterized by its distinctive kenozooidal ooecium. The new genus is also deemed to include Aplousina grandipora Moyano, an allied species from the Chilean con-tinental slope. Alderina simplicissima sp. nov., is also described from the Magellanic region.